Hubungan Antara Keterlibatan Ayah dalam Pengasuhan Terhadap Perilaku Prososial Gen-Z - Umi Mutoharoh; Andhita Dyorita Khoiryasdien (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the relationship between father’s involvement in parenting and prosocial behavior of Gen-Z in Indonesia. Prosocial behavior as an act of helping others without expecting direct benefits is an important aspect in the social dynamics of this generation. This study employed a quantitative correlational method with a sample of 100 Gen-Z people in Indonesia. Data collection was carried out using a measurement instrument for father’s involvement and prosocial behavior. The results of statistical analysis using the Spearman correlation test showed a significant positive relationship between father involvement in parenting and prosocial behavior in Gen-Z with a correlation coefficient value (r) of 0.428 (p = 0.000). This study provides practical implications on the importance of increasing awareness of the role of fathers in parenting as active figures in the development of children's character and social behavior, as well as the importance of developing family education programs that support father involvement in parenting.